2006
DOI: 10.1016/j.otohns.2006.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Complication rate of minimally invasive cochlear implantation

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 6 publications
6
59
0
2
Order By: Relevance
“…Using ST for CI can cause multiple complications, such as tissue devascularization, postoperative edema, and increased risk of infection and tissue necrosis [7,8]. Nowadays, some techniques, such as LIT, involving small incisions have been developed in order to disrupt a lesser amount of the soft tissue blood supply, decrease the amount of created dead space [8,9], and reduce the operative time [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using ST for CI can cause multiple complications, such as tissue devascularization, postoperative edema, and increased risk of infection and tissue necrosis [7,8]. Nowadays, some techniques, such as LIT, involving small incisions have been developed in order to disrupt a lesser amount of the soft tissue blood supply, decrease the amount of created dead space [8,9], and reduce the operative time [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, some techniques, such as LIT, involving small incisions have been developed in order to disrupt a lesser amount of the soft tissue blood supply, decrease the amount of created dead space [8,9], and reduce the operative time [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study published in 2000 reported operative time of 192-206 minutes and total anesthesia time of 249-269 minutes for unilateral CI. 3 An accurate estimation of the length of time required to perform CI would be valuable for costbenefit analysis, determining appropriate 3 rd party reimbursement, and determining if newer, less invasive techniques for CI, such as endaural, 4 suprameatal, 5,6 minimal access, [7][8][9][10] or percutaneous 11 approaches will provide a tangible benefit in terms of decreased operative time. Shorter surgical times translate into decreased duration of general anesthesia and decreased fees, critical factors in determining the overall cost-benefit analysis for a given procedure.…”
Section: Introductionmentioning
confidence: 99%